2017
DOI: 10.21767/2472-5056.100043
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy from RAAS to Autophagy: The Era for New Players

Abstract: Diabetic nephropathy is a leading cause of end-stage renal disease (ESRD) and increased cardiovascular morbidity and mortality worldwide in patients with type 2 diabetes mellitus. The mechanisms behind the pathophysiology of DN are complex and continue to be not fully understood. Both metabolic (hyperglycaemia) and haemodynamic alterations interact synergistically, and have been reported to activate local RAAS resulting in increased angiotensin-2. In spite the early and chronic treatment with converting enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Immunohistochemical results showed that cell loss in renal cortex of DN group is associated with significant decrease in H score of LC3 when compared with control group, which was consistent with previous results [46]. Impaired autophagy may be involved in the pathogenesis of podocyte loss, leading to massive proteinuria with progression of DN to end-stage renal failure [48]. Hyperglycemia inhibits Jun N-terminal kinase (JNK) signaling and enhances the interaction between Beclin-1 and Beclin-2 resulting in autophagy inhibition [49].…”
Section: Discussionsupporting
confidence: 90%
“…Immunohistochemical results showed that cell loss in renal cortex of DN group is associated with significant decrease in H score of LC3 when compared with control group, which was consistent with previous results [46]. Impaired autophagy may be involved in the pathogenesis of podocyte loss, leading to massive proteinuria with progression of DN to end-stage renal failure [48]. Hyperglycemia inhibits Jun N-terminal kinase (JNK) signaling and enhances the interaction between Beclin-1 and Beclin-2 resulting in autophagy inhibition [49].…”
Section: Discussionsupporting
confidence: 90%
“…The main pathological changes in DN include functional changes manifested by hyperfiltration and morphological changes in the glomerulus and proximal convoluted tubule (PCT) cells, with podocyte effusion, mesangial matrix hyperplasia, extracellular matrix (ECM) expansion, tubulointerstitial fibrosis, and glomerular sclerosis, leading to ESRD [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These lead to the release of reactive oxygen species and oxidative stress and inflammatory mediators. Several studies have demonstrated that inflammatory cytokines and proinflammatory factors are closely associated with DN generation and progression [ 6 , 7 ]. Moreover, it is known that renal fibrosis is caused by renal hemodynamic changes, ischemia, glucose metabolism abnormalities, and an overactive renin-angiotensin-aldosterone system (RAAS) [ 5 , 8 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With consequences of reactive oxygen species(ROS) generation, inflammation, over expression of transforming growth factor-β (TGF-β), and deregulations of different vascular growth factors such as the vascular endothelial growth factor-A (VEGF-A) (8) . Activating local (RAAS) results in increased angiotensin II (Ang II), in addition to action Adrenoctincorticotrpic hormone ( ACTH ), and potassium are three principal factors that adjusted aldosterone secretion (9,10) .…”
Section: Introductionmentioning
confidence: 99%